Design and Implementation of a Virtual Academic System at the Faculty of Industrial Engineering. UNMSM. - Raffo Lecca, Eduardo (2001)
In this age of information, where people live around the internet; many business activities are carried unaINTRANET. The aim is to have the current state of a company operacines day after day. In the academic field; Today it is important to build institutional portals, so that the student or graduate ehresado, can count on the timely and effective information. the objective of acad emic {virtual project is to have an intranet at the Faculty of Industrial Engineering, to have timely information from diverdas operations performed in the university; especially in the academic aspect of the assessment and to have this information in cualquien time.